The Possible Weakening of Financial Accounting from Tax Reforms - Hanlon, Michelle (The Accounting Review, 2021)
ABSTRACT There are past and proposed tax law changes that contain provisions that affect financial reporting. These include calls for book-tax conformity, proposals to increase the links between financial accounting and taxable incomes, and actions by Congress that make direct alterations to U.S. GAAP. I submit that these tax law changes potentially threaten financial reporting quality. I discuss my concerns about why such provisions have not attracted attention from accountants to the extent they should and make a case for more awareness and more research going forward.